Real‐time free‐breathing cardiac imaging with self‐calibrated through‐time radial GRAPPA. Issue 1 (10th March 2016) - Sayin, Ozan; Saybasili, Haris; Zviman, M. Muz; Griswold, Mark; Halperin, Henry; Seiberlich, Nicole; Herzka, Daniel A.
Abstract : Purpose: Real‐time free‐breathing cardiac imaging with highly undersampled radial trajectories has previously been successfully demonstrated using calibrated radial generalized autocalibrating partially parallel acquisition (rGRAPPA). A self‐calibrated approach for rGRAPPA is proposed that removes the need for the calibration prescan. Methods: To investigate the effect of various parameters on image quality, a comprehensive imaging study on one normal swine was performed. Root mean squared errors (RMSEs) were computed with respect to gold standard acquisitions, and several acquisition/reconstruction strategies were compared. Additionally, the method was tested on 13 human subjects, and RMSEs relative to standard through‐time radial GRAPPA were computed. Results: Real‐time images with high spatiotemporal resolution were obtained. Image quality was comparable to calibrated through‐time rGRAPPA with endocardial and epicardial borders clearly delineated. In the swine, the average RMSE between self‐calibrated and gold‐standard calibrated images was 5.18 ± 0.84%. In normal human subjects, the average RMSE between self‐calibrated and calibrated through‐time rGRAPPA was 3.79 ± 0.64%. For lower accelerations rates (R = 6‐8) image quality was similar to comparable calibrated scans though RMSE increased for higher degrees of undersampling (R = 12–16). Conclusion: Highly accelerated real‐time imaging with undersampled radial trajectories without additional calibration data is feasible. Image quality was acceptable for real‐time cardiac MRI applications demanding high speed. Magn Reson Med 77:250–264, 2017. © 2016 Wiley Periodicals, Inc.